Quality and reliability of trigger finger youtube videos - Uzel, Kadir; Yılmaz, Mehmet Kürşat; Çaçan, Mehmet Akif; Artuç, Merdan (EDRA S.p.A, 2023)
Introduction. Orthopedic video contents published on YouTube are not scanned and do not go through an editorial evaluation process. It is important to determine the quality and content accuracy of health-related videos. Trigger finger is a common disease and the deterioration in quality of life. However, the quality, content and adequacy of YouTube videos as a source of information about this disease have not been evaluated. The aim of this study is to investigate the quality and adequacy of the medical content of the videos on YouTube about trigger finger disease. Methods. In September 2022, the phrase “trigger finger” was entered in the YouTube search bar and the 50 most watched videos were included in the study, provided that the language of the video was English. Who uploaded the videos, real or animated content, number of views, upload date, number of comments, number of like-dislikes and video length were recorded. 3 orthopedic surgeons and 1 hand surgeon watched the videos simultaneously and separately. JAMA, DISCERN and GQS scores were calculated. Results. Average length of 50 videos is 321 seconds, number of views is 244,150, number of days from upload date to evaluation date is 1,789 days, VPI was 94, view ratio was 300. The average scores of 4 different surgeons from the parameters used for the quality and relevance analysis of the videos: JAMA 2, DISCERN 36, and GQS 2. The scores of 4 different surgeons were statistically compatible with each other (p = 0.000). The interclass correlation coefficient (ICC) was 0.906 for the JAMA score, 0.889 for the DISCERN score, and 0.831 for the GQS score. Conclusions. YouTube videos about trigger finger were low quality and unreliable. In the light of our study and other studies, the possibility of high-quality and reliable videos for patients can be increased by the evaluation and inspection of videos present-ed by YouTube.
Keywords: Patient Education; Quality; Reliability; Social Media; Trigger Finger; Youtube